(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
Oxidative stress plays the central role in the pathogenesis and progression of diabetic complications. The present study aims to investigate the beneficial effect of oral administration of flavone baicalein in streptozotocin-nicotinamide (STZ-NA) induced diabetic rats by measuring oxidative stress markers, antioxidant enzyme activities and expression analysis of antioxidant genes. Experimental diabetes was induced by a single intraperitoneal (i.p.) injection of STZ (55 mg /kg b.wt), 15 min after the i.p. administration of NA. At the end of the experimental period, thiobarbituric acid reactive substances (TBARS), activities of antioxidant enzymes and expression levels of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione peroxidase (GPx) were measured in diabetic rats along with serum biochemical parameters namely total cholesterol (TC), total triglyceride (TG), aspartate transaminase (AST) alanine transaminase (ALT) and glycosylated hemoglobin (HbA1c). Oral administration of baicalein (40 mg/kg b.wt/day) demonstrated a significant ameliorative effect on all studied biochemical and oxidative stress parameters. Biochemical findings were corroborated by qPCR expression analysis which showed significant upregulation of antioxidant genes in diabetic rats. These results suggest that baicalein supplementation may reduce diabetes and its complications by suppressing oxidative stress and enhancing gene expression and antioxidant enzyme activities in diabetic rats.